The impact of level 5 shared autonomous vehicles on suburbanization in Munich - Lorentz, Yannick (2023)
Shared autonomous vehicles (SAVs) with an autonomy level of 5 (full automation) are able to provide a combination of taxi-services and conventional car-sharing. The research presented in this dissertation focuses on understanding the perception of Munich residents towards the phenomenon of suburbanization by the introduction of SAVs. The results show that the introduction of SAVs with autonomy level 5 will still take a couple of years. The focus should now be on use cases for level 4 autonomous robo-buses, which are able to link not so well-connected localities to the public transportation system of Munich. The survey showed that (1) a decrease in fuel costs was the leading factor why Munich citizens would move out the city. Insights from literature about previous suburbanization as well as from expert and consumer interviews revealed that suburbanization in Munich will be driven by desire for (2) an increase in comfort,(3) a decrease in travel time and (4) a decrease in travel cost. The results from Munich were not applicable to other cities. Finally, SAVs will impact where citizens will be living in the future. Predicting an exact course of suburbanization in Munich was not possible. This newly generated knowledge is intended to serve as initial preliminary information for urban design and planning institutions.